The Combined Role of Extensive Reading and Extensive Viewing for Enhancing English Literature Students’ Literary Appreciation and Knowledge - Azizi , Neshat; Podpera, Rastislav; Stur, Martin; Obloberdiyevna, Djamaldinova Shakhlo (Journal of Education Culture and Society, 2024)
Aim. The extent to which extensive reading (ER) and extensive viewing (EV) combined can support literature students’ literary knowledge, particularly for EFL learners has yet to be established. Methods. This study undertakes a qualitative approach to understanding the opportunities that each of these modes provide for EFL literature students. The investigation was done through focus group interviews conducted at the end of the course, and student learning journals written every two weeks. The participants were a class of 36 sophomore English literature students. Extensive reading (ER) and extensive viewing (EV) were operationalised as books and movie adaptations of classic literature through reading or watching general fiction and movies. Results. The results indicated that ER/ EV were valuable for English literature students, and complemented each other. EV appeared to offer a visual coverage to ER which suggested that it could be an effective asset to be used along with extensive reading. Conclusion. The implications of the current study are for English literature students and teachers alike to consider this combination or each of these modes as a valuable source of input or practice.